2019
DOI: 10.1098/rspb.2018.2769
|View full text |Cite
|
Sign up to set email alerts
|

Why has transparency evolved in aposematic butterflies? Insights from the largest radiation of aposematic butterflies, the Ithomiini

Abstract: Defended species are often conspicuous and this is thought to be an honest signal of defences, i.e. more toxic prey are more conspicuous. Neotropical butterflies of the large Ithomiini tribe numerically dominate communities of chemically defended butterflies and may thus drive the evolution of mimetic warning patterns. Although many species are brightly coloured, most are transparent to some degree. The evolution of transparency from a warning-coloured ancestor is puzzling as it is generally assumed to be invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…This study is the first to investigate the benefit value of transparency in cryptic terrestrial prey and to experimentally isolate the effect of transparency from other aspects (as patch colour or patch size). Whether the position and the size of transparent windows, as well as the intrinsic optical properties of the transparent surface (levels of transmission and reflection briefly explored by Arias et al, and McClure et al, ) and its interaction with the ambient light (Johnsen & Widder, ), influence transparency efficiency also remains untested for terrestrial prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to investigate the benefit value of transparency in cryptic terrestrial prey and to experimentally isolate the effect of transparency from other aspects (as patch colour or patch size). Whether the position and the size of transparent windows, as well as the intrinsic optical properties of the transparent surface (levels of transmission and reflection briefly explored by Arias et al, and McClure et al, ) and its interaction with the ambient light (Johnsen & Widder, ), influence transparency efficiency also remains untested for terrestrial prey.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing detection of four real species of aposematic butterflies by predators, Arias et al () recently showed that even if all offered high visual contrast and were conspicuous to predators, fully opaque species were more detectable than species with transparent elements. In this case, transparency may help reducing detection in the first place, but if detected, butterflies may benefit from advertising their unpalatability with highly contrasting patches (McClure et al, ). However, in many species, transparency has evolved in already cryptic butterflies, as in the Neotropical moth Neocarnegia basirei (Saturniidae) or the Malaysian Carriola ecnomoda (Erebidae), where transparent wing areas are surrounded by brownish patches frequent in their visual background.…”
Section: Introductionmentioning
confidence: 99%
“…1A-H, [8][9][10]. This trait has been interpreted as an adaptation in the context of camouflage, in which some lineages evolved transparent wings as crypsis to reduce predation (11)(12)(13). Transparency results from the transmission of light across the visible spectrum through a material, in this case the chitin membrane, without appreciable absorption or reflection.…”
Section: Introductionmentioning
confidence: 99%
“…1G-I) (10,23). More recent studies have explored aspects of structural diversity, optical properties, phylogenetic distribution, and ecological relevance of transparency within a wide range of butterflies and moths, highlighting that transparency has evolved multiple times independently and may present evolutionary benefits (13,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, although most aposematic Lepidoptera species harbour brightly coloured patterns, some unpalatable, aposematic species exhibit transparent wing areas (McClure et al 2019). In those species, wing colour pattern typically consists in a mosaic of brightly coloured and transparent patches.…”
Section: Introductionmentioning
confidence: 99%